APLIKASI PUPUK KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN SEMAI JELUTUNG RAWA (Dyera lowii Hook.F) - Muhammad Abdi; Muhammad Mardhiansyah; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Most of the peat swamp forests have been degraded, one of the efforts in peat restoration was by replanting native peat plants. For conservation, it was necessary to cultivate Dyera lowii plants for the provision of good and quality seeds, using compost of oil palm empty bunches. The purpose of this study was to determine the effect of the application from compost of oil palm empty bunches as a medium to stimulate the growth of Dyera lowii seedlings. This research was conducted using a completely randomized design (CRD) consisting of four treatments and five replications, so that there were 20 experimental. The application of TKKS compost were : P1 = Without TKKS application, P2 = 20% TKKS compost + 80% peat soil, P3 = 50% TKKS compost + 50% peat soil, P4 = 80% TKKS compost + 20% soil peat. The data obtained from the research results were analyzed with variance using SPSS 20.0. Furthermore, if the results of the variance have a significant effect, further analysis will be carried out using the Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results showed that the application from compost of oil palm empty bunches had an effect on the dry weight of the Dyera lowii seedlings. The treatment level of 80% TKKS compost mixed with 20% peat soil showed the best treatment with a high yield as 0.87 cm, plant dry weight as 0.79 g and a root shoot ratio as 2.07. Keywords : Dyera lowii Hook.F, compost, oil palm empty bunches